2020
DOI: 10.1007/s10113-020-01698-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes of potential catches for North-East Atlantic small pelagic fisheries under climate change scenarios

Abstract: Small and intermediate-size pelagic fisheries are highly impacted by environmental variability and climate change. Their wide geographical distribution and high mobility makes them more likely to shift their distribution under climate change. Here, we explore the potential impact of different climate change scenarios on the four main commercial pelagic species in the North-East Atlantic (NEA): Atlantic mackerel (Scomber scombrus), European sprat (Sprattus sprattus), Atlantic herring (Clupea harengus) and blue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 145 publications
(170 reference statements)
0
1
0
Order By: Relevance
“…Studies have already shown changes to species distributions and communities in these waters (Beaugrand et al, 2009;Bedford et al, 2020;Chivers et al, 2017;Edwards et al, 2021;Simpson et al, 2011). Recent work indicates that fish species in the region will undergo poleward movements to track preferred thermal habitats under further warming (Cheung et al, 2010(Cheung et al, , 2011Fernandes et al, 2020;Jones et al, 2013), consistent with predictions across the globe (Cheung et al, 2009;Okunishi et al, 2012). However, due to highly specific depth and habitat requirements, the future distributions and abundance of species may be prevented from tracking their optimal thermal niche, including in the North Sea (Rutterford et al, 2015).…”
mentioning
confidence: 59%
“…Studies have already shown changes to species distributions and communities in these waters (Beaugrand et al, 2009;Bedford et al, 2020;Chivers et al, 2017;Edwards et al, 2021;Simpson et al, 2011). Recent work indicates that fish species in the region will undergo poleward movements to track preferred thermal habitats under further warming (Cheung et al, 2010(Cheung et al, , 2011Fernandes et al, 2020;Jones et al, 2013), consistent with predictions across the globe (Cheung et al, 2009;Okunishi et al, 2012). However, due to highly specific depth and habitat requirements, the future distributions and abundance of species may be prevented from tracking their optimal thermal niche, including in the North Sea (Rutterford et al, 2015).…”
mentioning
confidence: 59%